Resistência de união ao cisalhamento entre tubos ortodônticos e miniplacas de ancoragem esquelética colados com diferentes materiais - Meirelles, Lucas da Silva (2016)
Most anchorage miniplates that are currently used do not present orthodontic devices. Thus, orthodontists resort to creativity and utilize adaptations such as buttons, brackets or tubes bonded directly to miniplates, which makes them more versatile in terms of dental movement possibilities. The goal of this paper was to determine, in Megapascals (MPa), the strength that can be attributed to the bond between an anchorage miniplate and an orthodontic accessory united by different materials. The bond between the accessory and the miniplates was divided into two groups: Group 1 resin (Transbond XT®, 3M ESPE), 20 specimens; Group 2 Cyanoacrylate (Scoth Bond®, 3M ESPE), 20 specimens. The shearing strength test (Rcp) was performed on a universal testing machine EMIC DL-2000. The result was 2.28 ± 0.44 MPa for Group 1 and 4.90 ± 0.76 MPa for Group 2. Sample normality was verified through the Kolmogorov-Smirnov test. The comparison between the means for the variable response was carried out using the Student T test. There was a significant statistical difference between the groups; however, both materials showed higher strength than that needed for dental movement.